Recovery of health‐related quality of life in patients undergoing robot‐assisted radical cystectomy with intracorporeal diversion. (5th July 2021) - Abozaid, Mohammed; Tan, Wei Shen; Khetrapal, Pramit; Baker, Hilary; Duncan, Jacqueline; Sridhar, Ashwin; Briggs, Tim; Selim, Mohamed; Abdallah, Mohamed Marzouk; Elmahdy, Alaa Aldin; Elserafy, Fatma; Kelly, John D.
Abstract : Objective: To report the health‐related quality of life (HRQoL) after robot‐assisted radical cystectomy and intracorporeal urinary diversion (iRARC), and to identify factors impacting on return to baseline. Patients and Methods: Consecutive patients undergoing iRARC between January 2016 and December 2017 completed the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire 30‐item core (EORTC‐QLQ‐C30) and EORTC‐QLQ‐Muscle‐Invasive Bladder Cancer Module (EORTC‐QLQ‐BLM30) questionnaires before surgery and had a minimum of 12 months follow‐up postoperatively. Results: A total of 76 patients met the inclusion criteria at 12 months. Neobladder (NB) cases ( n  = 24) were younger (57.0 vs 71.0 years, P  < 0.001) and fitter than ileal conduit (IC) cases ( n  = 52), and had higher physical (100.0 vs 93.3, P  = 0.039) and sexual functioning (66.7 vs 50.0, P  = 0.013) scores at baseline. Longitudinal analysis of the EORTC‐QLQ‐C30 showed that physical (NB: 93.3 vs 100.0, P  = 0.020; IC: 80.0 vs 93.3, P  < 0.001) and role functioning scores (NB: 83.3 vs 100.0, P  = 0.010; IC: 83.3 vs 100.0, P  = 0.017) decreased and fatigue score (NB: 22.2 vs 11.1, P  = 0.026; IC: 33.3 vs 22.2, P  = 0.008) increased at 3 months in both diversion groups. Scores returned to baseline at 6 months except physical functioning score in IC patients that remained below baseline until 12 months (86.7 vs 93.3, P  = 0.012). The global HRQoL score did not show significant change postoperatively in both groups. A major 90‐day Clavien–Dindo complication was a significant predictor (odds ratio [OR] 0.11, 95% confidence interval [CI] 0.02–0.62; P  = 0.012) of deteriorated global HRQoL score at 3 months, while occurrence of a late complication (OR 0.14, 95% CI 0.03–0.65; P  = 0.013) was a predictor of deteriorated global HRQoL score at 12 months. Longitudinal analysis of the EORTC‐QLQ‐BLM30 showed that urinary problems (NB: 14.3 vs 38.3, P  < 0.001; IC: 5.6 vs 19.1, P  < 0.001) and future perspective (NB: 33.3 vs 44.4, P  = 0.004; IC: 22.2 vs 44.4, P  < 0.001) scores were better than baseline at 3 months. Sexual function deteriorated significantly at 3 months (NB: 8.3 vs 66.7, P  < 0.001; IC: 4.2 vs 50.0, P  < 0.001) and then showed improvement at 12 months but was still below baseline (NB: 33.3 vs 66.7, P  = 0.001; IC: 25.0 vs 50.0, P  < 0.001). Involvement in penile rehabilitation was shown to be a significant predictor (β 18.62, 95% CI 6.06–30.45; P  = 0.005) of higher sexual function score at 12 months. Conclusion: While most functional domains and symptoms scales recover to or exceed baseline within 6 months of iRARC, physical function remains below baseline in IC patients up to 12 months. Global HRQoL is preserved for both types of urinary diversion; however, postoperative complications seem to be the main driving factor for global HRQoL. Sexual function is adversely affected after iRARC suggesting that structured rehabilitation of sexual function should be an integral part of the RC pathway.